(untitled) (Research, Society and Development, 2017)
The main purpose of this paper is to calculate the estimation of oil supply and demand in the last 12 quarters (2013-2015), using an OLSconometric model, indicating the supply and demand of the market, in a second moment the oil market current supply and demand curves would be indicated for the average price of Brent oil in the abovementioned period. So that in a second moment the "dead weight" of OPEC’s economic price model is calculated and how this deadweight economically affects the oil and gas market globally, economically withdrawing the profits that the main producers could obtain if OPEC did not set the price artificially in unstable political scenarios. Lastly, regarding the global economy, and more precisely, the loss in the energy through financial results due the actions taken by OPEC led by Saudi Arabia and its partners in the Middle East, indicating the market failures caused by a cartel.